The Role of Activeness for Potentiating Learning in LMOOCs for Vulnerable Groups. Issue 1 (21st June 2021) - Read, Timothy; Barcena, Elena
In this article the authors present a new concept, activeness, as a dynamic psychological and cognitive state of effective engaged language learning. It is defined in terms of investment, integration and performance, and empowers vulnerable students to exercise control of their learning and progress based on their needs and desired outcomes. It is argued that activeness has a double didactic and linguistic dimension, implemented as a design feature in course materials and activities, and more importantly, promoted in forum communication. Therefore, participating in a strategically designed and scaffolded inclusive LMOOC can serve the triple purpose of enabling more effective target language learning, empowering vulnerable learners, and developing student potential to become engaged members of the language learning community. This engagement is arguably an important step towards doing the same in the real world. A study is presented of the second edition of an LMOOC on Spanish for immediate needs for vulnerable groups to explore the ways in which activeness was incorporated into the course and the effects it had. This research was conducted following a mixed-method approach which involved the platform's analytics, forum messages, pre- and post-questionnaires, and course observation. Evidence is provided of the progressive presence of activeness across different linguistic levels and the effect it had on students' satisfaction, course completion, and linguistic interaction. The results from this LMOOC provide evidence that it is possible to create a supportive online environment that meets the learning needs of vulnerable groups.